Post-discharge “continuum of care” clinical pathway for persons with severe neurodisabilities—qualitative research to assess its concept and practicality after implementation - Reichl, Stephanie; Pletz, Romy; Bartsch-de Jong, Aukje; Vallejo, Nuria; Groß, Tatjana; Bender, Andreas; Platz, Thomas (Frontiers in Neurology, 2025)
IntroductionThe aim of this study was to reflect the appropriateness and practicality of an evidence- and guideline-based clinical pathway (CP) for the intersectoral support of community-based neurorehabilitation of severely affected neurological patients requiring home-based intensive care nursing, early after its regional implementation in the Federal State of Bavaria, Germany. The CP is designed to support ongoing functional progress, with specialists from three regional neurological early rehabilitation centers (NER) providing rehabilitation expertise shared with healthcare professionals in the community across Bavaria, using a person-centered, individualized approach.MethodsQualitative exploratory study design: Semi-structured interviews with three NER-based regional outreach teams (ROFTs), followed by a multi-stage qualitative analysis and interpretation of their responses.ResultsThree group interviews were conducted with a total of 10 ROFT members. A total of 304 unique responses (i) were documented. Based on their experience, the teams reported numerous healthcare-related barrier observations (i = 69) and consequently, negative expectation reflections regarding the care situation in the community (i = 10). Regarding their outreach activities, the team’s observations predominantly indicated that their interventions were successful (i = 12). Nevertheless, negative expectation reflections regarding the CP’s implementation prevailed for both medical aspects (i = 27) and networking (i = 41).ConclusionAlthough the CP was not challenged conceptually by the field experience, the teams implementing the intersectoral collaboration faced major challenges with the continuum of care approach. Most importantly, a lack of, and variability in, qualified therapeutic resources, as well as the fact that multiprofessional team approaches were not established as a healthcare standard in the community, were noted. While the research findings support the need for a situation analysis and targeted implementation efforts, they also indicate the potential for such a hybrid collaborative center- and community-based healthcare approach for a clientele with highly specialized healthcare needs.